Molecular mitochondrial DNA and radiographic approaches for human archaeology identification - Rus Dina Rus Din; Shahrul Hisham Zainal Ariffin; Sahidan Senafi; Rohaya Megat Abdul Wahab; Intan Zarina Zainol Abidin (Universiti Kebangsaan Malaysia, 2014)
Ancient remains are considered very valuable artefacts, as they allow for the study of ancient cultures, phylogeny, evolution and the reconstruction of demographic history. To obtain all the information contained within remains, the investigation of such samples requires the expertise and various techniques from multiple fields of study. The present review focuses on the molecular biology and radiographic approaches used to identify ancient samples. Studies of ancient remains face various limitations; for example, the quality and quantity of the ancient samples can affect the difficulty of the investigations. Due to these limitations, new sophisticated techniques are being introduced to replace the earlier conventional techniques. A search was conducted using PubMed, Scopus, Science Direct and Science Finder to provide a new and timely review on the molecular mitochondrial DNA and radiographic analysis for human archaeology identification. The present review has determined that molecular biological approaches are very accurate and useful for the use in the ancestral determination of incomplete specimens, whereas observations of the dental pulp chamber are suitable for age at death estimations in both adults and children. However, these techniques are expensive and require expert personnel. Therefore, conventional approaches remain the favourite methods of most institutions, especially in Asia.